2022
DOI: 10.1177/10711007221077100
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific Instrumentation vs Standard Referencing in Total Ankle Arthroplasty: A Comparison of the Radiologic Outcome

Abstract: Background: Existing literature on the superiority of patient-specific instrumentation (PSI) in total ankle arthroplasty (TAA) over standard referencing (SR) is limited. Advantages presented include better implant alignment, shorter operating times, and increased accuracy of implant size prediction. The aim of this retrospective study was to analyze PSI in the hands of an experienced foot and ankle surgeon new to both PSI and SR for this specific implant, in regard to determining implant alignment, operative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…32 In a study comparing the use of PSI to a standard referencing guide (SRG), although no significant difference was found in tibial implant alignment, the PSI had significantly less operative and fluoroscopy time. 35 In contrast, the study by Heisler et al 25 showed that implant positioning was similar in both groups, and no advantage in regard to the operative time could be seen when comparing TAA using PSI to SRG.…”
Section: Discussionmentioning
confidence: 93%
“…32 In a study comparing the use of PSI to a standard referencing guide (SRG), although no significant difference was found in tibial implant alignment, the PSI had significantly less operative and fluoroscopy time. 35 In contrast, the study by Heisler et al 25 showed that implant positioning was similar in both groups, and no advantage in regard to the operative time could be seen when comparing TAA using PSI to SRG.…”
Section: Discussionmentioning
confidence: 93%
“…Limitations of CAS, such as in systems like the 3D CT O-Arm TM, include high cost, long operative time, and difficult justification of its use for more streamlined procedures where accuracy, triangulation, or trajectories are not difficult to achieve by the surgeon alone. PSI is also limited due to lack of data on longitudinal outcomes, and mixed results regarding implant position accuracy and fluoroscopy exposure [ 53 , 54 , 55 ]. Lastly, despite the precision offered by the future of robot-assisted TAA, there will be requirements for surgical flexibility as ankle pathology and biomechanical complexity frequently necessitates additional procedures such as MDCO for improved implant function, which could entail a higher economic burden and need for robot complexity [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative radiographic assessments of PSI have demonstrated reliable implant positioning (within 3–5 degrees deviation from planned), consistent neutral alignment (93.2–100%), and accurate component sizing (more accurate for tibial than talus component due to intraoperative variation in gutter debridement). However, small comparative studies between standard referencing (SR) and PSI, have found no significant improvements in implant positioning and mixed findings on other proposed benefits such as shorter operative length due to less fluoroscopy required with PSI [ 53 , 54 , 55 ]. As differences in longitudinal outcomes with PSI have also yet to be characterized, the current literature does not provide adequate evidence for widespread adoption of PSI in TAA to justify cost [ 52 , 56 , 57 ].…”
Section: Clinical Applications In Foot and Ankle Surgerymentioning
confidence: 99%
“…Positive outcomes of custom 3-D printed implants and instrumentation for ankle and hindfoot reconstruction have been reported. In a comparison of 24 ankle arthroplasty cases with patient-specific instrumentation and 25 cases with standard instrumentation, Heisler et al 37 found no difference between the techniques for component position or duration of the surgical procedure. All cases were performed by a single, experienced surgeon.…”
Section: Ankle Arthritis and Reconstructionmentioning
confidence: 99%